2018
DOI: 10.1530/erc-17-0542
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory thyroid cancer

Abstract: Distant metastases from thyroid cancer of follicular origin are uncommon. Treatment includes levothyroxine administration, focal treatment modalities with surgery, external radiation therapy and thermal ablation, and radioiodine in patients with uptake of 131 I in their metastases. Two thirds of distant metastases become refractory to radioiodine at some point, and when there is a significant tumor burden and documented progression on imaging, a treatment with a kinase inhibitor may provide benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 89 publications
4
41
0
1
Order By: Relevance
“… 5 PTC develops slowly and can be cured by surgery, thyroid hormone therapy and 131 I isotope therapy. 6 Most PTC patients have good prognosis with the 10-year survival rate reaching 90%. 7 , 8 Because of the serious potential side effects of radioactive iodine and patients’ neglect of the PTC prognosis, some PTC patients suffer from recurrence and some PTCs may develop distant metastases with high mortality.…”
Section: Introductionmentioning
confidence: 99%
“… 5 PTC develops slowly and can be cured by surgery, thyroid hormone therapy and 131 I isotope therapy. 6 Most PTC patients have good prognosis with the 10-year survival rate reaching 90%. 7 , 8 Because of the serious potential side effects of radioactive iodine and patients’ neglect of the PTC prognosis, some PTC patients suffer from recurrence and some PTCs may develop distant metastases with high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have not found any benefit for RAI treatment in terms of DFS or OS in low-risk patients (Lamartina et al 2015). On the other hand, the rare patients with evidence of structural residual disease after surgery are candidates for a high activity (3.7 GBq) RAI treatment (Berdelou et al 2018).…”
Section: Post-operative Administration Of Raimentioning
confidence: 99%
“…It included total thyroidectomy and post-operative administration of a high activity of radioactive iodine (RAI) followed by suppressive levothyroxine therapy (Mazzaferri & Jhiang 1994). This type of aggressive strategy is still appropriate for high-risk DTCs (Berdelou et al 2018, but for the vast majority of tumors currently diagnosed that have a low risk of mortality and of recurrence, there is no convincing evidence that aggressive treatment is beneficial (Hay et al 2018). Consequently, the current trend is toward the use of a more limited approach for these tumors, which still permits a reliable follow-up (Lamartina et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer (TC) is a very common endocrine malignancy, [ 1 3 ] which is characterized by different biological and clinical features. [ 4 6 ] It is also the leading cause of mortality and morbidity around the world. [ 7 – 8 ] It consists of 4 subtypes of papillary thyroid cancer, follicular thyroid cancer, medullary thyroid cancer, and anaplastic thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%